2020
DOI: 10.1371/journal.pone.0230030
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional neuroplasticity in newly arrived Middle Eastern refugees in the U.S.: Association with environmental exposures and mental health symptoms

Abstract: Background Psychological war trauma among displaced refugees is an established risk factor for mental health disorders, especially post-traumatic stress disorder (PTSD). Persons with traumainduced disorders have heightened neuroplastic restructuring of limbic brain circuits (e.g., amygdala and hippocampus), which are critical factors in the pathophysiology of PTSD. Civilians in war are exposed to both psychological trauma and environmental hazards, such as metals. Little is known about the possible mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…A number of studies have focused on the theme of cognition and the brain. The results show that factors, such as low cognitive ability/function, cognitive vulnerability, cognitive impairment or deficits, subjective cognitive decline, regression of dendritic branching and hippocampal atrophy/death of hippocampal cells, impaired neuroplasticity, and neurogenesis-related aspects, have been linked to depression [ 131 , 212 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 ]. The cognitive reserve appears to act as a moderator and can magnify the impact of certain determinants on poor mental health.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have focused on the theme of cognition and the brain. The results show that factors, such as low cognitive ability/function, cognitive vulnerability, cognitive impairment or deficits, subjective cognitive decline, regression of dendritic branching and hippocampal atrophy/death of hippocampal cells, impaired neuroplasticity, and neurogenesis-related aspects, have been linked to depression [ 131 , 212 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 ]. The cognitive reserve appears to act as a moderator and can magnify the impact of certain determinants on poor mental health.…”
Section: Resultsmentioning
confidence: 99%
“…However, neither of those studies measured self-reports of cognitive failure. A study of trauma-exposed refugees reported higher levels of brain derived neurotrophic growth factor (BDNF) and nerve growth factor (NGF), both of which were related to mental health outcomes [ 18 ]. These neurotrophins, biomarkers of neuroplasticity, could potentially affect cognitive function and ability in frontline nurses.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide substantial evidence of the physical and emotional strain experienced by nurses treating COVID patients. Sustained stress has been linked to neurocognitive dysfunction [ 17 , 18 ]. However, little is known regarding the impact of this occupational strain on nurses’ cognitive function at work.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems are reportedly among the most important and yet most neglected issues faced by displaced populations ( Al-Delaimy et al, 2020 ). People fleeing areas of armed conflict are at an elevated risk of experiencing issues such as post-traumatic stress disorder, depression, anxiety and suicide ( Al-Delaimy et al, 2020 ; Arnetz et al, 2020 ). The study of mental health issues in displaced populations is greatly complicated by the lack of appropriate psychological assessment tools to evaluate the effects of extreme forms of trauma often endured during armed conflict, such as kidnappings, assassinations, torture, genocide and mass rape ( Shultz et al, 2019 ; Brennan and Nandy, 2001 ).…”
Section: Population Displacementmentioning
confidence: 99%